Behaviour-based movement cut-off points in 3-year old children comparing wrist- with hip-worn actigraphs MW8 and GT3X - Daniel Jansson; Rikard Westlander; Jonas Sandlund; Christina E. West; Magnus Domellöf; Katharina Wulff (PLoS ONE, 2025)
Background Behaviour-based physical intensity evaluation requires rigorous calibration before application in long-term recordings of children’s sleep/activity patterns. This study aimed at (i) calibrating activity counts of motor behaviour measured simultaneously with MotionWatch 8 (MW8) and ActiGraph (GT3X) in 3-year-old children, (ii) documenting movement intensities in 30s-epochs at wrist/hip positions, and (iii) evaluating the accuracy of cut-off agreements between different behavioural activities. Methods Thirty 3-year-old children of the NorthPop cohort performed six directed behavioural activities individually, each for 8–10 minutes while wearing two pairs of devices at hip and wrist position. These naturally-occurring behaviours were aligned to movement intensities from ‘motionless’ (watching cartoons) and ‘sedentary’ (recumbent story listening, sit and handcraft) to ‘light activity’ (floor play with toys), ‘moderate activity’ (engaging in a brisk walk) and ‘vigorous activity (a sprinting game). Time-keeping was ensured using direct observation by an observer. Receiver-Operating-Curve classification was applied to determine activity thresholds and to assign two composite movement classes. Results Activity counts of MW8 and GT3X pairs of wrist-worn (rho =  0.94) and hip-worn (rho =  0.90) devices correlated significantly (p <  0.001). Activity counts at hip position were significantly lower compared to those at the wrist position (p <  0.001), irrespective of device type. Sprinting, floorball/walk and floorplay assigned as ‘physically mobile’ classes achieved outstanding accuracy (AUC > 0.9) and two sedentary and a motionless activities assigned into ‘physically stationary’ classes achieved excellent accuracy (AUC > 0.8). Conclusion This calibration provides useful cut-offs for physical activity levels of preschool children. Contextual information of behaviour is advantageous over intensity classifications only, because interventions will focus on behaviour-allocated time to reduce a sedentary lifestyle. Our comparative calibration is one step forward to behaviour-based movement guidelines for 3-year-old children.